LEGAL PROTECTION FOR INDONESIAN MIGRANT WORKERS FOR SEXUAL CRIMES EXPERIENCED AT WORK (CASE STUDY OF SEXUAL CRIMES EXPERIENCED BY ERY IN TAIWAN) - Puspita, Enny Ika; Nurtjahyo, Lidwina Inge (Sean Institute, 2022)
This study aims to determine the form of legal protection for, Indonesian Migrant Workers for sexual crimes experienced at work, Knowing the factors that cause people to be interested in becoming Indonesian Migrant Workers and the obstacles of the Indonesian government through Indonesian representatives in handling cases experienced by Ery as an Indonesian Migrant Worker in Taiwan, This research includes the type of empirical juridical research, data collection with literature studies, The results show that law enforcement and human rights protection in each country are still not running well but Indonesia has provided assistance in the form of providing legal assistance, such as the case experienced by Ery as an Indonesian Migrant Worker in Taiwan who received sexual crimes from the employer, Although Ery is reluctant to tell this because she has a lot of debt so she is afraid that if she is returned to Indonesia, Ery is also embarrassed considering the culture in her hometown, people think women who have been fenced are dirty.